Vital democracy a theory of democracy in action - Hendriks, Frank, 1966- (Oxford : Oxford University Press, 2010)
This text outlines a theory of democracy in action, based on four elementary forms of democracy - pendulum, consensus, voter and participatory democracy - that are thoroughly analysed compared and related to both the literature and the real world of democracy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democracy; Representative government and representation